Money and central bank digital currency - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2019)
This study reviews the concepts and features of both central bank and private sector money and focuses on them in selected advanced and emerging economies. As a newly emerged form of private sector money, digital coins (cryptoassets) such as bitcoin have garnered much attention because their underlying distributed ledger technology enables decentralized verification while maintaining features similar to cash. Some central banks have expressed unease about digital coins because of their high volatility. However, digital coins are limited in their use as a payment tool. Thus, it is likely to take time before digital coins are a threat to commercial and central banks. Meanwhile, some central banks have examined the potential application of distributed ledger technology and the issuing of their own digital coins to the general public or financial institutions - the so-called central bank digital currency initiatives. So far, no central banks have found strong advantages to this because of several technical constraints. Given that the technology has progressed quickly, it is possible that central banks may increase their interest in digital currency proposals based on distributed ledger technology. Meanwhile, Sweden's Riksbank has initiated a separate move by considering the issuance of deposit accounts and prepaid payment methods to the general public in the face of declining cash use. Other central banks have shown little interest in the Swedish initiative because of the potential adverse impacts on the banking system caused by a shift in retail deposits from commercial banks to the central bank.
Keywords: E42; E44; E51; 330; Money; central bank digital currency; cash; digital coins; bank deposits